Self-supporting negative electrode material and preparation method and application thereof
By using polyaniline to coat the phosphorus carbon/graphene aerogel self-supporting negative electrode material in the black phosphorus battery material, the problems of low black phosphorus conductivity and large volume expansion are solved, and the high specific capacity and good cycle stability of lithium/sodium ion batteries are achieved.
Patent Information
- Application Number
- CN202411855900.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-29
AI Technical Summary
As the negative electrode material of lithium/sodium ion batteries, black phosphorus has problems with low electronic conductivity and large volume expansion, resulting in mechanical fracture, electrical contact loss and instability in the solid electrolyte phase interface, thereby reducing the cycle life of the battery.
The phosphorus-carbon composite material is coated by in-situ polymerization of aniline and added graphene oxide for heating reduction to form a polyaniline-coated aerogel self-supporting negative electrode material coated with phosphorus-carbon/graphene.
This material exhibits high specific capacity and good cycling stability in lithium-ion and sodium-ion batteries, and improves electron transport and mechanical strength by forming phosphorus-carbon bonds and porous network-like structures.
Smart Images

Figure CN119905546A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials for lithium / sodium ion batteries, and in particular to a self-supporting negative electrode material and a preparation method and application thereof. Background Art
[0002] With the continuous development of battery technology, the demand for lithium-ion batteries (LIBs) and sodium-ion batteries (NIBs) with high energy density and long cycle life is gradually increasing, and the main factor affecting battery performance depends on the electrode material.
[0003] Among them, the negative electrode material in the electrode material is usually black phosphorus, which is a very promising negative electrode material with a high theoretical specific capacity (2596mAh / g). + / Na + A three-electron alloying reaction occurs to generate Li3P / Na3P. However, black phosphorus has low electronic conductivity and a volume change of more than 300% occurs during the alloying reaction. Therefore, severe mechanical fracture and electrical contact loss may occur during the charge and discharge process. At the same time, repeated expansion / contraction will also make it impossible for the electrode to form a stable solid electrolyte interface (SEI) film, continuously consuming the electrolyte and the negative electrode Li + , resulting in a decrease in Coulombic efficiency, which in turn causes the material's specific capacity to decay during the cycle and reduces the battery's cycle life.
[0004] Currently, the most common strategy to improve the low electrical conductivity and large volume expansion of black phosphorus is to use carbonaceous materials and phosphorus to form a composite material, and use the resulting phosphorus-carbon composite material as the negative electrode. However, this method is generally effective in reducing the expansion of black phosphorus and forming a stable solid electrolyte phase interface, and cannot effectively improve the specific capacity and cycle stability of the material. Summary of the invention
[0005] The embodiment of the present application provides a self-supporting negative electrode material and its preparation method and application. By providing a preparation method of a polyaniline-coated phosphorus carbon / graphene aerogel self-supporting negative electrode material that does not require the use of a current collector, a binder, a conductive additive and other materials, the electrode material is used in lithium-ion and sodium-ion batteries and has a higher specific capacity and better cycle stability.
[0006] In order to solve the above technical problems, in the first aspect, an embodiment of the present application provides a method for preparing a self-supporting negative electrode material, comprising the following steps: first, polyaniline is coated on a phosphorus-carbon composite material by in-situ polymerization of aniline to obtain a dispersion of polyaniline-coated phosphorus-carbon; then, graphene oxide is added to the dispersion of polyaniline-coated phosphorus-carbon, and heated and reduced to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel; finally, the polyaniline-coated phosphorus-carbon / graphene aerogel is sliced to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel self-supporting negative electrode.
[0007] In some exemplary embodiments, the phosphorus-carbon composite material is prepared by the following method: zirconium oxide balls are added to black phosphorus and graphite powder for ball milling to obtain the phosphorus-carbon composite material; wherein the mass ratio of black phosphorus to graphite powder is 1.5 to 9, the diameter of the zirconium oxide balls is 2 mm to 15 mm, the ball-to-material ratio is 15:1 to 80:1, the rotation speed is 100 rpm to 600 rpm, and the ball milling time is 1 h to 72 h.
[0008] In some exemplary embodiments, the black phosphorus is selected from at least one of micron-sized black phosphorus powder, black phosphorus thin film, black phosphorus nanosheets, and black phosphorus quantum dots.
[0009] In some exemplary embodiments, the graphite powder is selected from at least one of nanographite powder, graphene microplatelets, and graphene nanoplatelets.
[0010] In some exemplary embodiments, polyaniline is coated on a phosphorus-carbon composite material by in-situ polymerization of aniline to obtain a dispersion of polyaniline-coated phosphorus-carbon, including: dispersing 10 mg to 200 mg of the phosphorus-carbon composite material in a solution containing 1 mg to 20 mg of aniline and 10 mg to 100 mg of protonic acid to prepare a solution A, and ultrasonically dispersing the solution A; slowly adding 1 mg to 30 mg of a persulfate solution to the ultrasonically dispersed solution A in an ice bath environment, filling with argon and slowly stirring to obtain a dispersion of polyaniline-coated phosphorus-carbon.
[0011] In some exemplary embodiments, the mass ratio of aniline to protonic acid is 1:1.5 to 1:16, the concentration of the persulfate solution is 5 mg / mL to 50 mg / mL, the dispersion concentration of the phosphorus-carbon composite material is 1 mg / mL to 50 mg / mL, and the ice bath temperature is 0°C to 15°C.
[0012] In some exemplary embodiments, the protic acid is one of hydrochloric acid, phosphoric acid, phytic acid, or acetic acid.
[0013] In some exemplary embodiments, graphene oxide is added to a dispersion of polyaniline-coated phosphorus carbon and heated for reduction to obtain a polyaniline-coated phosphorus carbon / graphene aerogel, including: adding an aqueous solution of graphene oxide to the dispersion of polyaniline-coated phosphorus carbon, filling with argon gas and sealing, heating and reducing the aqueous solution of graphene oxide to obtain a polyaniline-coated phosphorus carbon / graphene hydrogel; cleaning and freeze-drying to obtain a polyaniline-coated phosphorus carbon / graphene aerogel.
[0014] In some exemplary embodiments, the volume of the graphene oxide aqueous solution is 2 mL to 10 mL, the concentration thereof is 2 mg / mL to 15 mg / mL, the heating temperature is 50° C. to 120° C., and the heating time is 1 h to 10 h.
[0015] In some exemplary embodiments, the mass ratio of polyaniline-coated phosphorus carbon to graphene oxide is 1:1 to 10:1, and the mass of graphene oxide accounts for 15% to 30% of the mass of the polyaniline-coated phosphorus carbon / graphene self-supporting negative electrode.
[0016] In a second aspect, the embodiments of the present application further provide a self-supporting negative electrode material, which is prepared using the method for preparing the self-supporting negative electrode material described in the above embodiments.
[0017] In addition, an embodiment of the present application also provides an application of the self-supporting negative electrode material as described in the above embodiment in lithium-ion and sodium-ion batteries.
[0018] The technical solution provided by the embodiment of the present application has at least the following advantages:
[0019] The embodiment of the present application provides a self-supporting negative electrode material and a preparation method and application thereof, the method comprising the following steps: first, polyaniline is coated on a phosphorus-carbon composite material by in-situ polymerization of aniline to obtain a dispersion of polyaniline-coated phosphorus-carbon; then, graphene oxide is added to the dispersion of polyaniline-coated phosphorus-carbon, and heated and reduced to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel; finally, the polyaniline-coated phosphorus-carbon / graphene aerogel is sliced to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel self-supporting negative electrode.
[0020] The embodiment of the present application provides a self-supporting negative electrode material and its preparation method and application. On the one hand, the polyaniline-coated phosphorus carbon / graphene aerogel self-supporting negative electrode provided by the present application can be directly used as an electrode, without the need to use the inactive component slurry such as the current collector, binder, conductive additive, etc., which can reduce the cost of preparation. On the other hand, the polyaniline-coated phosphorus carbon / graphene aerogel self-supporting material prepared by the present application has a high specific capacity and good cycle stability when applied to lithium-ion and sodium-ion batteries. Thanks to the formed phosphorus-carbon bond, the edge reconstruction can be prevented and effective lithium / sodium ion insertion and diffusion can be ensured. The polyaniline coating can be used as a carbon layer to alleviate the volume expansion of black phosphorus, and also promote the formation of a stable SEI film. The graphene aerogel with a porous network structure can form a stable conductive carbon layer network. The two carbon layers are in close contact, which is conducive to the transmission of electrons, thereby improving the reaction kinetics. At the same time, this structure is also conducive to maintaining the mechanical strength of the self-supporting electrode and accommodating the stress generated during the cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplifications do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.
[0022] Figure 1A schematic diagram of the preparation process of a self-supporting negative electrode material and its preparation method and application provided in an embodiment of the present application.
[0023] Figure 2 This is a flow chart of the polyaniline-coated phosphorus carbon / graphene hydrogel prepared in Example 2 of the present application.
[0024] Figure 3 This is a digital picture of the polyaniline-coated phosphorus carbon / graphene hydrogel prepared in Example 2 of the present application.
[0025] Figure 4 This is a scanning electron microscope image of the polyaniline-coated phosphorus carbon / graphene aerogel prepared in Example 2 of the present application.
[0026] Figure 5 It is a conductivity diagram of the materials prepared in Example 2, Control Example 1 and Example 1 of the present application under different pressures.
[0027] Figure 6 This is a cycle performance diagram of Example 2, Control Example 1 and Example 1 of the present application when used as negative electrode materials for lithium-ion batteries.
[0028] Figure 7 This is a cycle performance diagram of Example 2, Control Example 1 and Example 1 of the present application when used as negative electrode materials for sodium ion batteries. DETAILED DESCRIPTION
[0029] As can be seen from the background technology, the most common strategy to improve the low electrical conductivity and large volume expansion of black phosphorus is to use carbonaceous materials and phosphorus for compounding. However, this method is generally effective in reducing the expansion of black phosphorus and forming a stable solid electrolyte phase interface.
[0030] In order to solve the above technical problems, the embodiment of the present application provides a self-supporting negative electrode material and its preparation method and application, the method comprising the following steps: first, polyaniline is coated on the phosphorus-carbon composite material by in-situ polymerization of aniline to obtain a dispersion of polyaniline-coated phosphorus-carbon; then, graphene oxide is added to the dispersion of polyaniline-coated phosphorus-carbon, and heated and reduced to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel; finally, the polyaniline-coated phosphorus-carbon / graphene aerogel is sliced to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel self-supporting negative electrode. The present application provides a method for preparing a polyaniline-coated phosphorus-carbon / graphene aerogel self-supporting negative electrode material that does not require the use of current collectors, binders, conductive additives and other materials. The electrode material is used in lithium-ion and sodium-ion batteries and has a higher specific capacity and better cycle stability.
[0031] The following will describe the various embodiments of the present application in detail with reference to the accompanying drawings. However, it will be appreciated by those skilled in the art that in the various embodiments of the present application, many technical details are provided in order to enable the reader to better understand the present application. However, even without these technical details and various changes and modifications based on the following embodiments, the technical solution claimed in the present application can be implemented.
[0032] See also Figure 1 The present invention provides a method for preparing a self-supporting negative electrode material, comprising the following steps:
[0033] Step S1, coating polyaniline on the phosphorus-carbon composite material by in-situ polymerization of aniline to obtain a dispersion of polyaniline-coated phosphorus-carbon.
[0034] Step S2, adding graphene oxide to the dispersion of polyaniline-coated phosphorus carbon, and heating and reducing the dispersion to obtain polyaniline-coated phosphorus carbon / graphene aerogel.
[0035] Step S3, slicing the polyaniline-coated phosphorus carbon / graphene aerogel to obtain a polyaniline-coated phosphorus carbon / graphene aerogel self-supporting negative electrode.
[0036] In some embodiments, the phosphorus-carbon composite material in step S1 is prepared by the following method: zirconium oxide balls are added to black phosphorus and graphite powder for ball milling to obtain a phosphorus-carbon composite material; wherein the mass ratio of black phosphorus to graphite powder is 1.5 to 9, the diameter of the zirconium oxide balls is 2 mm to 15 mm, the ball-to-material ratio is 15:1 to 80:1, the rotation speed is 100 rpm to 600 rpm, and the ball milling time is 1 h to 72 h.
[0037] In some embodiments, the black phosphorus is selected from at least one of micron-sized black phosphorus powder, black phosphorus film, black phosphorus nanosheets, and black phosphorus quantum dots; the graphite powder is selected from at least one of nanographite powder, graphene microsheets, and graphene nanosheets.
[0038] The method for preparing the self-supporting negative electrode material provided in the embodiment of the present application, and its specific preparation flow chart are as follows: Figure 2 As shown, black phosphorus and graphite powder are ball-milled at a certain mass ratio to obtain a phosphorus-carbon composite material; a layer of polyaniline is coated by in-situ polymerization of aniline to obtain a polyaniline-coated phosphorus-carbon dispersion. Then, graphene oxide is added and heated for reduction, and then washed and freeze-dried to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel. Finally, the polyaniline-coated phosphorus-carbon / graphene aerogel is cut into small pieces of several millimeters in thickness and rolled into thin sheets of hundreds of microns to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel self-supporting negative electrode, which is applied to lithium-ion and sodium-ion batteries respectively.
[0039] Specifically, the ball milling process is as follows: the mixture of black phosphorus and graphite powder is sealed in a zirconium oxide tank filled with argon gas, the tank is filled with zirconium oxide balls with a diameter of 2 mm to 15 mm, and the ball-to-material ratio is 15:1 to 80:1. A planetary ball mill is used, and the ball milling is performed at a speed of 100 rpm to 600 rpm for 1 hour to 72 hours.
[0040] It should be noted that when a layer of polyaniline is coated by in-situ polymerization of aniline, the concentration of proton acid during the in-situ polymerization process will affect the conductivity, ammonium persulfate will affect whether polyaniline can be formed, and the amount of aniline will affect the thickness of the coating layer.
[0041] Then add graphene oxide, heat and reduce, wash and freeze-dry to obtain polyaniline-coated phosphorus carbon / graphene aerogel. Due to the strong protonicity of polyaniline, the reduced polyaniline can provide H+ and electrons to reduce the oxygen-containing groups of graphene oxide. In aqueous solution, the hydrophilic graphene oxide is reduced to hydrophobic reduced graphene oxide, which will spontaneously aggregate to form a stable three-dimensional network structure, while tightly wrapping the equally hydrophobic polyaniline-coated phosphorus carbon core. The actual picture of adding graphene oxide dispersion and self-assembly to form a hydrogel is shown in the figure. Figure 3 shown.
[0042] In some embodiments, step S1 coats polyaniline on the phosphorus-carbon composite material by in-situ polymerization of aniline to obtain a dispersion of polyaniline-coated phosphorus-carbon, comprising: dispersing 10 mg to 200 mg of the phosphorus-carbon composite material in a solution containing 1 mg to 20 mg of aniline and 10 mg to 100 mg of protonic acid to prepare a solution A, and ultrasonically dispersing the solution A; slowly adding 1 mg to 30 mg of persulfate solution to the ultrasonically dispersed solution A in an ice bath environment, filling with argon and slowly stirring to obtain a dispersion of polyaniline-coated phosphorus-carbon.
[0043] In some embodiments, the mass ratio of aniline to protonic acid is 1:1.5 to 1:16, the concentration of the persulfate solution is 5 mg / mL to 50 mg / mL, the dispersed concentration of the phosphorus-carbon composite material is 1 mg / mL to 50 mg / mL, and the ice bath temperature is 0°C to 15°C.
[0044] In some embodiments, the protic acid is one of hydrochloric acid, phosphoric acid, phytic acid, or acetic acid.
[0045] Step S2: adding graphene oxide to a dispersion of polyaniline-coated phosphorus carbon and heating and reducing the dispersion to obtain a polyaniline-coated phosphorus carbon / graphene aerogel, comprising the following steps:
[0046] Step S201, adding a graphene oxide aqueous solution to a dispersion of polyaniline-coated phosphorus carbon, filling with argon gas and sealing, and heating to reduce the graphene oxide aqueous solution to obtain a polyaniline-coated phosphorus carbon / graphene hydrogel.
[0047] Step S202, clean and freeze-dry to obtain polyaniline-coated phosphorus carbon / graphene aerogel.
[0048] The preparation method of the polyaniline-coated phosphorus carbon / graphene aerogel self-supporting negative electrode provided in the present application, wherein the cleaning described in step S202 is to pour out the original solution, soak it in deionized water for 10min to 100min, and repeat it several times. The freeze-drying process is: the washed polyaniline-coated phosphorus carbon / graphene hydrosol is frozen and pretreated at a temperature of -75℃ to -80℃ for 1h to 5h. Then, evacuate to an air pressure below 0.01Pa, freeze-dry for 24h to 30h, and obtain the polyaniline-coated phosphorus carbon / graphene aerogel.
[0049] In some embodiments, the volume of the graphene oxide aqueous solution in step S201 is 2 mL to 10 mL, the concentration thereof is 2 mg / mL to 15 mg / mL, the heating temperature is 50° C. to 120° C., and the heating time is 1 h to 10 h.
[0050] In some embodiments, in step S2, the mass ratio of polyaniline-coated phosphorus carbon to graphene oxide is 1:1 to 10:1.
[0051] In some embodiments, in step S3, the mass of graphene oxide accounts for 15% to 30% of the mass of the polyaniline-coated phosphorus carbon / graphene self-supporting negative electrode.
[0052] The preparation method of the self-supporting negative electrode material provided in the present application is described in detail below through specific examples.
[0053] Example 1
[0054] Step 1, black phosphorus and graphite powder are mixed in a mass ratio of 8:2. 2 g of the mixture of black phosphorus and graphite is sealed in a zirconium oxide can filled with argon gas, and the can is filled with zirconium oxide balls with diameters of 5 mm and 2 mm, and the ball-to-material ratio is 80:1. Planetary ball milling is used for 12 hours at a speed of 400 revolutions per minute to obtain a phosphorus-carbon composite material;
[0055] Step 2, disperse 100 mg of the phosphorus-carbon composite material in 8 mL of deionized water containing 15 mg of aniline and 72 mg of phytic acid (solution A). Ultrasonicate for 1 minute to evenly disperse solution A. Dissolve 13.6 mg of ammonium persulfate in 1.2 mL of deionized water (solution B). Cool solution A and solution B in an ice bath for 10 minutes. Then, in an ice bath environment, slowly drip solution B into solution A. Then fill with argon and slowly stir for 6 hours. Obtain a dispersion of polyaniline-coated phosphorus-carbon;
[0056] Step 3, drying the dispersion to obtain a polyaniline-coated phosphorus-carbon negative electrode.
[0057] Example 2
[0058] Step 1, black phosphorus and graphite powder are mixed in a mass ratio of 8:2. 2 g of the mixture of black phosphorus and graphite is sealed in a zirconium oxide can filled with argon gas, and the can is filled with zirconium oxide balls with diameters of 5 mm and 2 mm, and the ball-to-material ratio is 80:1. Planetary ball milling is used for 12 hours at a speed of 400 revolutions per minute to obtain a phosphorus-carbon composite material;
[0059] Step 2: Disperse 100 mg of the phosphorus-carbon composite material in 8 mL of deionized water containing 15 mg of aniline and 72 mg of phytic acid (solution A). Ultrasonicate for 1 minute to disperse solution A evenly.
[0060] Step 3, 13.6 mg of ammonium persulfate was dissolved in 1.2 mL of deionized water (solution B). Solution A and solution B were cooled in an ice bath for 10 minutes. Then, solution B was slowly dripped into solution A in an ice bath. Then argon gas was filled and slowly stirred for 6 hours. A dispersion of polyaniline-coated phosphorus carbon was obtained;
[0061] Step 4, adding 5 mL of a 5 mg / mL graphene oxide (GO) aqueous solution to the polyaniline-coated phosphorus carbon dispersion, filling with argon gas and sealing, heating to 90° C. and keeping warm for 2 hours to reduce the graphene oxide to graphene, and obtaining a polyaniline-coated phosphorus carbon / graphene hydrogel;
[0062] Step 5: freeze-dry the polyaniline-coated phosphorus carbon / graphene hydrogel, cut it into small pieces, and roll it into thin sheets to obtain a polyaniline-coated phosphorus carbon / graphene self-supporting electrode.
[0063] Example 3
[0064] Step 1, dispersing 100 mg of the phosphorus-carbon composite material in a solution containing 1 mg of aniline and 72 mg of phytic acid protonic acid to prepare a solution A, and performing ultrasonic dispersion on the solution A;
[0065] Step 2, slowly adding 13.6 mg of persulfate solution into the ultrasonically dispersed solution A in an ice bath environment, filling with argon gas and slowly stirring to obtain a dispersion of polyaniline-coated phosphorus carbon;
[0066] Step 3, drying the dispersion to obtain a polyaniline-coated phosphorus-carbon negative electrode.
[0067] Example 4
[0068] Step 1, dispersing 100 mg of the phosphorus-carbon composite material in a solution containing 20 mg of aniline and 72 mg of phytic acid protonic acid to prepare a solution A, and performing ultrasonic dispersion on the solution A;
[0069] Step 2, slowly adding 13.6 mg of persulfate solution into the ultrasonically dispersed solution A in an ice bath environment, filling with argon gas and slowly stirring to obtain a dispersion of polyaniline-coated phosphorus carbon;
[0070] Step 3, drying the dispersion to obtain a polyaniline-coated phosphorus-carbon negative electrode.
[0071] Example 5
[0072] Step 1, dispersing 100 mg of the phosphorus-carbon composite material in a solution containing 15 mg of aniline and 10 mg of phytic acid protonic acid to prepare a solution A, and performing ultrasonic dispersion on the solution A;
[0073] Step 2, slowly adding 13.6 mg of persulfate solution into the ultrasonically dispersed solution A in an ice bath environment, filling with argon gas and slowly stirring to obtain a dispersion of polyaniline-coated phosphorus carbon;
[0074] Step 3, drying the dispersion to obtain a polyaniline-coated phosphorus-carbon negative electrode.
[0075] Example 6
[0076] Step 1, dispersing 100 mg of the phosphorus-carbon composite material in a solution containing 15 mg of aniline and 50 mg of phytic acid protonic acid to prepare a solution A, and performing ultrasonic dispersion on the solution A;
[0077] Step 2, slowly adding 13.6 mg of persulfate solution into the ultrasonically dispersed solution A in an ice bath environment, filling with argon gas and slowly stirring to obtain a dispersion of polyaniline-coated phosphorus carbon;
[0078] Step 3, drying the dispersion to obtain a polyaniline-coated phosphorus-carbon negative electrode.
[0079] Example 7
[0080] Step 1, dispersing 100 mg of the phosphorus-carbon composite material in a solution containing 15 mg of aniline and 100 mg of phytic acid protonic acid to prepare a solution A, and performing ultrasonic dispersion on the solution A;
[0081] Step 2, slowly adding 13.6 mg of persulfate solution into the ultrasonically dispersed solution A in an ice bath environment, filling with argon gas and slowly stirring to obtain a dispersion of polyaniline-coated phosphorus carbon;
[0082] Step 3, drying the dispersion to obtain a polyaniline-coated phosphorus-carbon negative electrode.
[0083] Example 8
[0084] Step 1, mixing black phosphorus and graphite powder by ball milling in a mass ratio of 8:2 to obtain a phosphorus-carbon composite material;
[0085] Step 2, dispersing 100 mg of the phosphorus-carbon composite material in a solution containing 15 mg of aniline and 72 mg of protonic acid to prepare a solution A, and performing ultrasonic dispersion on the solution A;
[0086] Step 3, slowly adding 13.6 mg of persulfate solution into the ultrasonically dispersed solution A in an ice bath environment, filling with argon gas and slowly stirring to obtain a dispersion of polyaniline-coated phosphorus carbon;
[0087] Step 4, adding 2 mL of a 5 mg / mL graphene oxide (GO) aqueous solution to the polyaniline-coated phosphorus carbon dispersion, filling with argon and sealing, heating to 90° C. and keeping warm for 2 hours to reduce the graphene oxide to graphene, obtaining a polyaniline-coated phosphorus carbon / graphene hydrogel, washing and freeze-drying to obtain a polyaniline-coated phosphorus carbon / graphene aerogel;
[0088] Step 5: Slice the polyaniline-coated phosphorus carbon / graphene aerogel to obtain a polyaniline-coated phosphorus carbon / graphene aerogel self-supporting negative electrode.
[0089] Example 9
[0090] Step 1, mixing black phosphorus and graphite powder by ball milling in a mass ratio of 8:2 to obtain a phosphorus-carbon composite material;
[0091] Step 2, dispersing 100 mg of the phosphorus-carbon composite material in a solution containing 15 mg of aniline and 72 mg of protonic acid to prepare a solution A, and performing ultrasonic dispersion on the solution A;
[0092] Step 3, slowly adding 13.6 mg of persulfate solution into the ultrasonically dispersed solution A in an ice bath environment, filling with argon gas and slowly stirring to obtain a dispersion of polyaniline-coated phosphorus carbon;
[0093] Step 4, adding 6 mL of a 5 mg / mL graphene oxide (GO) aqueous solution to the polyaniline-coated phosphorus carbon dispersion, filling with argon and sealing, heating to 90° C. and keeping warm for 2 hours to reduce the graphene oxide to graphene, obtaining a polyaniline-coated phosphorus carbon / graphene hydrogel, washing and freeze-drying to obtain a polyaniline-coated phosphorus carbon / graphene aerogel;
[0094] Step 5: Slice the polyaniline-coated phosphorus carbon / graphene aerogel to obtain a polyaniline-coated phosphorus carbon / graphene aerogel self-supporting negative electrode.
[0095] Comparative Example 1
[0096] Black phosphorus and graphite powder are ball-milled in a certain mass ratio to obtain a phosphorus-carbon composite material A, and A is mixed with a conductive additive, a binder and N-methylpyrrolidone to form a slurry to obtain a negative electrode material 1.
[0097] It is worth noting that in Control Example 1, only a phosphorus-carbon composite material was synthesized and the phosphorus-carbon composite material was used as the negative electrode. In Example 1 of the present application, a polyaniline-coated phosphorus-carbon composite material was synthesized on the basis of the phosphorus-carbon composite material. The phosphorus-carbon bond formed by polyaniline-coated phosphorus-carbon can prevent edge reconstruction and ensure effective lithium / sodium ion insertion and diffusion. The polyaniline coating can serve as a carbon layer to alleviate the volume expansion of black phosphorus and promote the formation of a stable SEI film, so that it has a high specific capacity and good cycle stability. Figure 6 The lithium-ion battery performance test results shown are: the specific capacity of Example 1 is maintained at 80.17%, and the coulombic efficiency is 99.20%, which is higher than that of Control Example 1 (specific capacity retention rate is 42.46%, and coulombic efficiency is 98.80%). Figure 7 The sodium ion battery test results shown: the specific capacity of Example 1 is maintained at 39.83%, and the coulombic efficiency is 98.10%, which is higher than that of Control Example 1 (the specific capacity is maintained at 28.78%, and the coulombic efficiency is 98.00%).
[0098] In Example 2 of the present application, a step of graphene oxidation is added relative to Example 1, and the formed aniline-coated phosphorus carbon / graphene aerogel has a porous network structure and can form a stable conductive carbon layer network, such as Figure 4 As shown in the scanning electron microscope, the phosphorus-carbon composite material is evenly distributed on the network structure of graphene oxide and polyaniline coating layer. The graphene oxide and polyaniline coating layer are closely combined, which is conducive to the transmission of electrons, such as Figure 5 As shown in the powder conductivity graph, based on Control Example 1, in Example 1, when the variable is the addition of polyaniline coating, the conductivity does not increase significantly with the increase of pressure, which may be because a good conductive network has not been formed. In Example 2, when the variable is polyaniline coating and graphene oxide is added, the conductivity increases significantly with the increase of pressure, indicating that a good conductive network has indeed been constructed. This porous network structure and conductive carbon layer network improve the reaction kinetics. At the same time, this structure is also conducive to maintaining the mechanical strength of the self-supporting electrode and accommodating the stress generated during the cycle, thereby improving the specific capacity and cycle stability of the negative electrode. Therefore, Figure 6 The lithium ion battery cycle performance and coulombic efficiency shown in Example 2, the initial discharge capacity of Example 2 is 1266.00 mAh / g, after 140 cycles, the specific capacity is maintained at 93.01%, and the coulombic efficiency is 99.40%, which is higher than that of Example 1 (the specific capacity retention rate is 42.46%, and the coulombic efficiency is 98.80%). Figure 7The sodium ion battery cycle performance and coulombic efficiency shown in Example 2 are that after 120 cycles, the specific capacity is 746.11 mAh / g and the coulombic efficiency is 63.98%, which are higher than Example 1 (the specific capacity remains at 39.83% and the coulombic efficiency is 98.10%).
[0099] Examples 3 and 4 changed the quality of aniline based on the ball milling of Example 1. Within the experimental range, the coating had an improvement effect, but the small amount of coating in Example 3 would lead to uneven coating, and the large amount of coating in Example 4 would lead to an overly thick coating layer, affecting ion / electron transmission. Therefore, it was finally determined that the quality of aniline in Example 1 was the best.
[0100] Based on the ball milling of Example 1, Examples 5, 6 and 7 changed the mass of phytic acid. Too little or too much phytic acid in Examples 5, 6 and 7 would affect the conductivity of the formed polyaniline coating. Therefore, it was finally determined that the mass of phytic acid in Example 1 was the best.
[0101] Compared with Example 2, Examples 8 and 9 changed the volume of the graphene oxide (GO) aqueous solution. In Example 8, the added volume of graphene oxide was small, resulting in loose contact with the polyaniline coating layer and loss of electronic electrical contact; in Example 9, the added volume of graphene oxide was large, resulting in fewer active sites and affecting the capacity, so it was finally determined that the volume of graphene oxide in Example 2 was the best.
[0102] Based on the above technical scheme, the embodiment of the present application provides a self-supporting negative electrode material and a preparation method and application thereof, the method comprising the following steps: first, polyaniline is coated on a phosphorus-carbon composite material by in-situ polymerization of aniline to obtain a dispersion of polyaniline-coated phosphorus-carbon; then, graphene oxide is added to the dispersion of polyaniline-coated phosphorus-carbon, and heated and reduced to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel; finally, the polyaniline-coated phosphorus-carbon / graphene aerogel is sliced to obtain a polyaniline-coated phosphorus-carbon / graphene aerogel self-supporting negative electrode.
[0103] The embodiment of the present application provides a self-supporting negative electrode material and its preparation method and application. On the one hand, the polyaniline-coated phosphorus carbon / graphene aerogel self-supporting negative electrode provided by the present application can be directly used as an electrode, without the need to use the inactive component slurry such as the current collector, binder, conductive additive, etc., which can reduce the cost of preparation. On the other hand, the polyaniline-coated phosphorus carbon / graphene aerogel self-supporting material prepared by the present application has a high specific capacity and good cycle stability when applied to lithium-ion and sodium-ion batteries. Thanks to the formed phosphorus-carbon bond, the edge reconstruction can be prevented and effective lithium / sodium ion insertion and diffusion can be ensured. The polyaniline coating can be used as a carbon layer to alleviate the volume expansion of black phosphorus, and also promote the formation of a stable SEI film. The graphene aerogel with a porous network structure can form a stable conductive carbon layer network. The two carbon layers are in close contact, which is conducive to the transmission of electrons, thereby improving the reaction kinetics. At the same time, this structure is also conducive to maintaining the mechanical strength of the self-supporting electrode and accommodating the stress generated during the cycle.
[0104] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.
Claims
1. A method for preparing a self-supporting negative electrode material, characterized in that: The following steps are involved: Polyaniline is coated on the phosphorus-carbon composite material by in-situ polymerization of aniline to obtain a dispersion of polyaniline-coated phosphorus-carbon; Adding graphene oxide to the dispersion of polyaniline-coated phosphorus carbon and heating for reduction to obtain polyaniline-coated phosphorus carbon / graphene aerogel; The polyaniline-coated phosphorus carbon / graphene aerogel is sliced to obtain a polyaniline-coated phosphorus carbon / graphene aerogel self-supporting negative electrode.
2. The method for preparing a self-supporting negative electrode material according to claim 1, characterized in that: The phosphorus-carbon composite material is prepared by the following method: Zirconium oxide balls are added to black phosphorus and graphite powder for ball milling to obtain a phosphorus-carbon composite material; The mass ratio of the black phosphorus to the graphite powder is 1.5 to 9, the diameter of the zirconia ball is 2 mm to 15 mm, the ball-to-material ratio is 15:1 to 80:1, the rotation speed is 100 rpm to 600 rpm, and the ball milling time is 1 h to 72 h.
3. The method for preparing a self-supporting negative electrode material according to claim 2, characterized in that: The black phosphorus is selected from at least one of micron-sized black phosphorus powder, black phosphorus film, black phosphorus nanosheets and black phosphorus quantum dots; the graphite powder is selected from at least one of nanographite powder, graphene microsheets and graphene nanosheets.
4. The method for preparing a self-supporting negative electrode material according to claim 1, characterized in that: The method of coating polyaniline on the phosphorus-carbon composite material by in-situ polymerization of aniline to obtain a dispersion of polyaniline-coated phosphorus-carbon comprises: Dispersing 10 mg to 200 mg of the phosphorus-carbon composite material in a solution containing 1 mg to 20 mg of aniline and 10 mg to 100 mg of protonic acid to prepare a solution A, and performing ultrasonic dispersion on the solution A; 1 mg to 30 mg of persulfate solution is slowly added to the ultrasonically dispersed solution A in an ice bath environment, and argon gas is filled and slowly stirred to obtain a dispersion of polyaniline-coated phosphorus carbon.
5. The method for preparing a self-supporting negative electrode material according to claim 4, characterized in that: The mass ratio of aniline to protonic acid is 1:1.5-1:16, the concentration of the persulfate solution is 5 mg / mL-50 mg / mL, the dispersion concentration of the phosphorus-carbon composite material is 1 mg / mL-50 mg / mL, and the ice bath temperature is 0°C-15°C.
6. The method for preparing a self-supporting negative electrode material according to claim 5, characterized in that: The protonic acid is one of hydrochloric acid, phosphoric acid, phytic acid or acetic acid.
7. The method for preparing a self-supporting negative electrode material according to claim 1, characterized in that: The method of adding graphene oxide to a dispersion of polyaniline-coated phosphorus carbon and heating and reducing the dispersion to obtain a polyaniline-coated phosphorus carbon / graphene aerogel comprises: adding a graphene oxide aqueous solution to the dispersion of polyaniline-coated phosphorus carbon, filling with argon gas and sealing, heating and reducing the graphene oxide aqueous solution to obtain a polyaniline-coated phosphorus carbon / graphene hydrogel; and washing and freeze-drying the dispersion to obtain a polyaniline-coated phosphorus carbon / graphene aerogel.
8. The method for preparing a self-supporting negative electrode material according to claim 7, characterized in that: The volume of the graphene oxide aqueous solution is 2 mL to 10 mL, the concentration is 2 mg / mL to 15 mg / mL, the heating temperature is 50° C. to 120° C., and the heating time is 1 h to 10 h.
9. A self-supporting negative electrode material, characterized in that: The self-supporting negative electrode material is prepared by the preparation method of any one of claims 1 to 8.
10. Use of the self-supporting negative electrode material according to claim 9 in lithium ion and sodium ion batteries.
Citation Information
Patent Citations
Graphene polyaniline composite and preparation method thereof, and lithium ion battery
CN103165898A
Graphene-based flexible self-supporting binderless electrode composite material and preparation method thereof
CN109037611A
Phosphorus-carbon composite material, preparation method and application
CN116598457A
Polymer-coated phosphorus-carbon composite material as well as preparation method and application thereof
CN117476896A
Lithium iron phosphate conductive aerogel as well as preparation method and application thereof
CN119059507A
Cited By
A self-supporting sodium-ion battery electrode material and a sodium-ion battery
CN122532170A